The influence of WB-EMS-Training on the performance of ice hockey players of different competitive status - Schuhbeck, E.; Birkenmaier, C.; Schulte-Göcking, H.; Pronnet, A.; Jansson, V.; Wegener, B. (Frontiers in Physiology, 2019)
Purpose: The aim of this study was to examine the influence of long-term whole-body electromyostimulation (WB-EMS) training in addition to standard ice hockey training in the following areas: shot speed, counter-movement-jump (CMJ) height and power, 10 m-sprint, isokinetic maximum force at 60 and 300°/s of the knee extensor muscle and subjective performance. The purpose was further to check, whether competitive status influenced the extent of response to WB-EMS and whether WB-EMS would hypothetically be a suitable method to reduce injury rate. Methods: Thirty male amateur ice hockey players participated in this study. They were divided into two cross-over groups (Group A and Group B). EMS sessions were carried out once a week for 12 weeks for each group with a subsequent 4 week EMS pause. The sessions consisted of 20 min electromyostimulation with 150 contractions (4 s duration, 85 Hz). Shot speed of slap shot was measured with Sportradar 1503. Jumping ability was determined with a ground reaction force platform (GRFP). Sprint time for 10 m skate was recorded using an infrared photo sensor. Isokinetic force of the knee extensor muscle was detected with Isomed 2000 at two different angular velocities (60 and 300°/s) and the subjective performance was collected using a questionnaire. Results: After 12 weeks of WB-EMS training jumping power increased significantly for the WB-EMS groups by 5.15%, 10 m skating time decreased significantly by 5%, and maximum isokinetic force at 300°/s increased significantly by 7% (all p < 0.05). In contrast post training shot speed showed no significant change. Isokinetic torque at 60°/s and vertical jump height were collected as secondary variables and showed increases of 5.45 and 15.15%, respectively. After finishing the WB-EMS and continuing the normal training, it was shown that the training effect regressed. Conclusion: This study demonstrated that WB-EMS training significantly decreased 10 m skating time and increased jumping power and maximum isokinetic force at 300°/s. We conclude that with additional WB-EMS training, an increase in performance might also be achieved for athletes in lower leagues. Due to the higher training potential of leisure athletes, the effect is probably even more pronounced than would be expected for competitive athletes.